Neurocognitive testing in the emergency department: A potential assessment tool for mild traumatic brain injury. (3rd September 2018) - Lunter, Catherine M; Carroll, Ellen L; Housden, Charlotte; Outtrim, Joanne; Forsyth, Faye; Rivera, Annie; Maimaris, Chris; Boyle, Adrian; Sahakian, Barbara J; Menon, David K; Newcombe, Virginia FJ
Abstract: Objective: Despite mild traumatic brain injury (mTBI) accounting for 80% of head injury diagnoses, recognition of individuals at risk of cognitive dysfunction remains a challenge in the acute setting. The objective of this study was to evaluate the feasibility and potential role for computerised cognitive testing as part of a complete ED head injury assessment. Methods: mTBI patients ( n = 36) who incurred a head injury within 24 h of presentation to the ED were compared to trauma controls ( n = 20) and healthy controls ( n = 20) on tests assessing reaction time, speed and attention, episodic memory, working memory and executive functioning. Testing occurred during their visit to the ED at a mean of 12 h post‐injury for mTBI and 9.4 h for trauma controls. These tasks were part of the Cambridge Neuropsychological Test Automated Battery iPad application. Healthy controls were tested in both a quiet environment and the ED to investigate the potential effects of noise and distraction on neurocognitive function. Results: Reaction time was significantly slower in the mTBI group compared to trauma patients ( P = 0.015) and healthy controls ( P = 0.011), and deficits were also seen in working memory compared to healthy controls ( P ≤ 0.001) and in executive functioning ( P = 0.021 and P < 0.001) compared to trauma and healthy controls. Performances in the control group did not differ between testing environments. Conclusion: Computerised neurocognitive testing in the ED is feasible and can be utilised to detect deficits in cognitive performance in the mTBI population as part of a routine head injury assessment.